2022
DOI: 10.1055/a-1981-3213
|View full text |Cite
|
Sign up to set email alerts
|

Scope and Limitations of the Palladium-Catalyzed Direct 1,2-Diheteroarylation of 1,2-Dihalobenzene Derivatives

Abstract: The reactivity of 1,2-dihalobenzenes in the palladium-catalyzed C-H bond functionalization is more difficult to control than that of 1,3- and 1,4-dihalobenzenes because of a possible Pd 1,4-migration during the second catalytic cycle. With C3-substituted heteroarenes this Pd 1,4-migration is not possible and the reaction allows the synthesis of a wide variety of functionalized 1,2-heteroarylated benzene derivatives in high yields. Conversely, only a few heteroarenes with a free C3-position such as thiazoles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…We have recently reported that in the course of the heteroarylation of 1,2-dihalobenzenes by thiophenes, a partial Pd 1,4-migration occurred 12,13 in some cases, leading to a mixture of 1,2-diheteroarylated benzenes and also to aryl-substituted biheteroarenes such as 2′-aryl-2,3′-bithiophenes. 14 This Pd 1,4-migration on thiophene derivatives provides an appealing method for functionalizing the C–H bonds at the β-position of thiophenes which are often more difficult to activate than those at the α-position. 15 In addition, so far, the preparation of 2′-aryl-2,3′-bithiophene derivatives requires multi-step synthesis and the substrate scope is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported that in the course of the heteroarylation of 1,2-dihalobenzenes by thiophenes, a partial Pd 1,4-migration occurred 12,13 in some cases, leading to a mixture of 1,2-diheteroarylated benzenes and also to aryl-substituted biheteroarenes such as 2′-aryl-2,3′-bithiophenes. 14 This Pd 1,4-migration on thiophene derivatives provides an appealing method for functionalizing the C–H bonds at the β-position of thiophenes which are often more difficult to activate than those at the α-position. 15 In addition, so far, the preparation of 2′-aryl-2,3′-bithiophene derivatives requires multi-step synthesis and the substrate scope is very limited.…”
Section: Introductionmentioning
confidence: 99%